Structural Assessment Of Distressed Bridges As An Aid To Development Of An Expert System - Chong, Kau Ping (2001)
The aim of this project is to develop a knowledge-base system to provide the rating system in analysing the effect of the various distresses on the structural behaviour of the deteriorated reinforced concrete beams bridge. This knowledge-base system is prepared for the “ Structural Assessment” part and use in an overall Comprehensive Expert System for bridge conditional assessment and evaluate the residual life of the bridge. In addition, the knowledge-base system also can also help the experts in making decision/rating during the earlt Condition Assessment stage. In this investigation, the structural reponse of reinforced concrete beams bridge subjected to loss of concrete under JKR-SV loading is presentes. The JKR-SV loading is adopted in this analysis because it provides the most critical load effect on the overall performance of the bridge. The problem most commonly found in bridges that are subjected to high commercial enviroment or overloaded i.e cracking, crushing and spalling of the cover to the reinforcement has been simulated by loss of concrete. The study in this project focuses on the effect of the location, length of losses and depth of the concrete loss on the structural behaviour of reinforced concrete beam. The effect of the bridge span, dimension of the beams and the amount of tension steel to the structural performance of the reinforced concrete beam under JKR-SV loading were also been taken into consideration. Non-linear analysis using finite element (FEM) had been carrying out to take care about the material non-linearity. In the analysis, 2 fields of consideration had been made: i) Yielding stresses of the bottom reinforcement at the location of maximum content. ii) Vertical displacement, Dy at the mid-span of the beam. The yielding load has been adopted as a failure criteria and deflection at JKR-SV load were compared with a control beam having no defect. Based on the results obtained from the finite element analysis, a new rating scheme had been proposed considering the serviceability and strength requirement of the beam. By using Visual basic, a knowledge-base system had been developed to expert opinions on the structural behaviour for the deteriorated reinforced concrete beam bridges. Finally, this user-friendly system is used to assist an engineer in analysing the effect of the variation distress on the load carrying of the bridges.